Influence of soy lecithin concentration on the physical properties of whey protein isolate-stabilized emulsion and microcapsule formation. (August 2017) - Wang, Shujie; Shi, Yan; Tu, Zongcai; Zhang, Lu; Wang, Hui; Tian, Ming; Zhang, Nanhai
Abstract: The effects of soy lecithin concentration on the physical properties of whey protein isolate (WPI) stabilized emulsion and the corresponding microcapsules obtained by spray drying were investigated. Results showed that the addition of lecithin reduced the droplet size and interfacial viscoelastic properties of the emulsion. The ζ-potential of the oil/water emulsion initially decreased and then increased with increasing soy lecithin concentration. The emulsion stability depended on the interaction between lecithin and whey protein isolate (WPI) on the interface, which formed a compact adsorption to response external deformations and thus enhanced the stability of emulsion. Microcapsules, obtained by spray drying of emulsion, exhibited good redispersibility in water. Scanning electron micrographs showed that the particles prepared by addition of lecithin showed compact surface. High encapsulation efficiency was observed at intermediate soy lecithin concentration (0.50–1.00%) because of the synergistic effect of lecithin and WPI in this region. Highlights: The interaction of lecithin-WPI has a significant influence on emulsion properties. High encapsulation efficiency of microcapsules relies on lecithin-WPI interactions. The mixed system may be applied to obtain microcapsules with desirable properties.